An Investigation of Ethical Leadership Approach of Elementary School Leaders in Madinah in Saudi Arabia 1440 - Ghawanni, Bayan Mansour (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the reality of the practice of moral leadership by primary school leaders in Madinah, and to compare the moral leadership relationship of the primary school leader in Madinah and the impact of variables of years of experience in education, as well as the type of school, whether governmental or private. The study used the descriptive survey method and a questionnaire as a tool designed by the researcher, consisting of 30 phrases divided into three axes that were distributed to a random sample of (30) school leaders using the statistical program (SPSS). The results of the study showed that the leaders of primary schools in Madinah have an average degree of practicing moral leadership skills. The results of the study also revealed that there were no statistically significant differences at the level (α≤0.05) between the sample answers regarding the reality of practicing ethical leadership according to the variables of the number of years of experience, or the type of school. These results are in broad agreement with what other researchers have found in their studies. Based on the results, the researcher recommended training school leaders or candidates to lead schools on moral leadership skills because of the importance of their presence and their positive impact on the school environment.
Keywords: ethical leadership; school leaders; primary girls schools; Madinah; Saudi Arabia